Effectiveness of Assertiveness Training Programme on Improving Self- Esteem Among Early Adolescents (International Journal of Nursing Education, 2022)
The Study was conducted to evaluate the effectiveness of assertiveness training programme on improving selfesteemamong early adolescents. Pre experimental one group pre-test, post-test design was utilized to performthe study with simple random sampling technique. Data were collected from the early adolescents betweenthe age group of 11 to 13 years who fulfilled the inclusion criteria through Rosenberg self esteem Scale. Thefindings revealed that the paired‘t’ test value for Self -esteem score was 28.09 which was significant at p≤0.05and was highly significant at p≤0.01, p≤0.001. It showed that assertiveness training programme was effective onimproving self- esteem among the early adolescents.